PWE-034 Hospitalisation for PBC: A UK-PBC Analysis of Hospital Episodes. (17th August 2016) - Hirschfield, G; Vale, L; Mells, G; Shapiro, D; Jones, D
Abstract : Introduction: The advent of new therapies for patients with primary biliary cirrhosis (PBC, also known as primary biliary cholangitis) highlights the need to understand the current health burden of PBC. This analysis assesed the frequency and nature of hospitalisations associated with PBC. Methods: UK-PBC analysed all records from 2009 through 2014 in the Hospital Episodes Statistics database, containing information on all hospitalisation across the National Health Service in England, where the ICD-10 code for PBC (K74.3) appeared as a primary or secondary diagnosis. We characterised primary diagnosis for each hospitalisation. Results: There were 21, 275 admissions with a PBC code over the 5 year observational period covering 1631 unique ICD-10s listed as the primary hospitalisation code. PBC was the primary code for 17% of admissions. The number of relevant hospitalisations increased from 3368 in 2009/2010 to 4995 in 2013/2014. The number per 100, 000 hospitalisations increased from 23 to 32 over this period (Figure ). The increase was almost completely driven by hospitalisations for which PBC was a secondary diagnosis. Liver transplants represented 5–10% of admissions with PBC as a primary code, and 1–2% of any PBC-related admission. The top 20 primary diagnoses when PBC is secondary included known sequelae of PBC: ascites (1.9% of total admissions), varices (1.3%), and liver cancer (1.3%). Remaining codes included: anaemia (iron deficiency and unspecified; 2.9%); respiratory (pneumonia, COPD and lower respiratory infections; 3.0%); osteoporosis and fractures (1.9%); and various abdominal (unspecified abdominal pain, gastritis and gastroenteritis; 1.5%). Conclusion: Our UK-PBC data confirms a significant clinical need for patients with PBC, including a rising healthcare burden attributed to disease. The increase in PBC-related diagnoses may be due to more accurate coding, greater co-morbidity as the result of increased longevity, or may represent the true impact of disease. New therapies preventing the progression of PBC to end-stage cirrhosis, and its complications, may help to reduce this rising burden. Disclosure of Interest: None Declared